Spectroscopic and crystallographic characterization of a tetrameric hemoglobin oxidation reveals structural features of the functional intermediate relaxed/tense state - L. Vitagliano; G. Smulevich; B. Howes; G. di Prisco; C. Verde; VERGARA, ALESSANDRO; BONOMI, GIOVANNA; MERLINO, ANTONELLO; MAZZARELLA, LELIO (Journal of the American Chemical Society, 2008)
Tetrameric hemoglobins represent the most commonly used model for the description of the basic concepts of protein allostery. The classical stereochemical model assumes a concerted transition of the protein, upon oxygen release, from the relaxed (R) to the tense (T) state. Despite the large amount of data accumulated on the end-points of the transition, scarce structural information is available on the intermediate species along the pathway. Here we report a spectroscopic characterization of the autoxidation process of the Trematomus newnesi major Hb component and the atomic resolution structure (1.25 Å) of an intermediate form along the pathway characterized by a different binding and oxidation state of the R and chains. In contrast to the R-heme iron, which binds a CO molecule, the iron displays a pentacoordinated oxidized state, which is rare in tetrameric hemoglobins. Interestingly, the information provided by the present analysis is not limited to the characterization of the peculiar oxidation process of Antarctic fish hemoglobins. Indeed, this structure represents the most detailed snapshot of hemoglobin allosteric transition hitherto achieved. Upon ligand release at the heme, a cascade of structural events is observed. Notably, several structural features of the tertiary structure of the R and chains closely resemble those typically observed in the deoxygenated state. The overall quaternary structure also becomes intermediate between the R and the T state. The analysis of the alterations induced by the ligand release provides a clear picture of the temporal sequence of the events associated with the transition. The implications of the present findings have also been discussed in the wider context of tetrameric Hbs.